Electrocatalytic Oxidation and Determination of Cysteine at Oxovanadium(IV) Salen Coated Electrodes - Piyush Kumar Sonkar; Vellaichamy Ganesan; Vijay Rao (International Journal of Electrochemistry)
A transition metal complex, oxovanadium(IV) salen (where salen represents N,N′-bis(salicylidene)ethylenediamine) is immobilized on glassy carbon (GC) electrodes and utilized for electrocatalytic oxidation of cysteine. In presence of oxovanadium(IV) salen, increased oxidation current is observed due to the effective oxidation of cysteine by the electrogenerated oxovanadium(V) salen species. The oxidation current linearly varies with the concentration of cysteine from 0.1 to 1.0 mM. The modified electrode has good sensitivity and low limit of detection. These properties make the oxovanadium(IV) salen as an effective electrocatalyst for the determination of cysteine.